LEARNING STRATEGIES TO DEVELOP SPEAKING SKILL: A CASE STUDY OF GOOD ORAL COMPETENT STUDENTS OF SENIOR HIGH SCHOOL IN INDONESIA - Alif Okta Shofia; Hikmah Pravitasari (English Didactic, 2020)
This research is about the analysis of learning strategy used by good oral competent students in speaking skill. The learning strategy is based on the Oxford’s classification of language learning strategy. The objectives of the research are to identify learning strategies used by good oral competent students, to analyze factors that contribute to the choice of learning strategies used by good oral competent students, to identify the dominant strategies used by good oral competent students, to identify the similarities and the differences of learning strategies used by good oral competent students. This is qualitative research which focuses on case study research. The participants of the research are two good oral competent students of MAN Karanggede which are choosed based on the observation, documentation and the criteria of good language learners. The data are collected from questionnaire and interview. The findings show that good oral competent students applied six types of learning strategy proposed by Oxford. The difference learning strategy used by two good oral competent students is on frequency of use learning  strategy.  The  factors  that  contribute  to  the  choice  of  learning strategies are level of language learning proficiency, cognitive or learning style, attitude and motivation, personality and teacher influences. The dominant learning strategy used by good oral competent students is compensation strategy which student 1 includes in high use and student 2 in medium use. Two good oral competent students of MAN Karanggede have same similarities that are the highest mean score of learning strategy use is compensation  strategy and  the  lowest  mean  score  is  social  strategy.  The second strategy which is frequently used by student 1 is metacognitive strategy, but student 2 frequently uses memory strategy.